KINERJA DAN MUTU PELAYANAN KESEHATAN RSUD DR. H. MOCH. ANSARI SALEH BANJARMASIN - Suryadi Ariyanto (STIA Bina Banua Banjarmasin, 2018)
This research is motivated by public service performed by government personnel in hospitals Dr. H. Moch . Ansari Saleh Banjarmasin in the health care section, that basically for people who didn`t get any right for equality service in Helath Care section. Furthermore Discrimination in care service above, especially among people who are able and indicates poor still lack the accountability. Hospital to the public as mandated by Law No. 36 Year 2009 on Health. A good quality service care and Low Cost treatment, as well as the attitude of the medical staff is friendly and communicative demands of the majority of patients to the hospital. There are so many complains and Quality of service for people who indicates poor didn`t get any responsible service. This research for identification any obstacles factor improving performance the hospital to improve the quality of public health service quality. The research hypothesis is one of the characteristics of survey research is to apply a quantitative approach, the file and information gathered through the case study method is a phenomenon that captured the perceptions and expectations of hospital performance in providing services. Based file collection and reporting as well as support dokomen questionnaires. By using the method of assessment checklist. The process of file analysis starts from the social approach, and to obtain comparative results are also used file analysis tools such as the proportion in percentage. Based on the research, the study result conclude that the hospital performance or IKM of the hospital Dr. H. Moch. Ansari Saleh Banjarmasin valued 68,4. With good quality service performance category. Even more about Quality of IKM performance was Valued 64,41. And get Good Quality performance. But for system threadment level was in 59,81. That values are from interval conversion 43,76 – 62,50, similliar with Kepmenpan No : KEP/25/M.PAN/2/2004, with categories Less Under/ C. This means that the factor is the bottleneck of the performance of the hospital Dr H.Moch.Ansari Saleh Banjarmasin in implementing health services to the community, so it affects the level of performance and quality of service . Suggested in improving Quality of Service Quality and Performance Hospital to get the value of